MENTAL AND BEHAVIOURAL PROBLEMS IN INDIA: A REVIEW STUDY (International Journal of Food and Nutritional Sciences, 2022)
The review was conducted to assess the burden of mental disorders and to study various issues and challenges at the community level. We searched electronic databases for studies related to the prevalence of various psychiatric morbidities and associated factors at the community level. The World Health Organization has estimated that mental and behavioural disorders account for about 12 percent of the global burden of diseases. The burden of mental and behavioural disorders in India ranges from 9.5 to 102 per 1000 population. The burden of mental disorders seen by the world is only a small part of the iceberg. Various studies have shown that the prevalence of mental disorders is higher among women, the elderly, disaster survivors, industrial workers, children, adolescents and people with chronic medical conditions. There is a need for improved living conditions, political commitment, primary health care and women empowerment.